Lineage analysis reveals an endodermal contribution to the vertebrate pituitary - Fabian, Peter; Tseng, Kuo-Chang; Smeeton, Joanna; Lancman, Joseph J; Dong, P Duc Si; Cerny, Robert; Crump, J Gage (Science (New York, N.Y.), 2020)
Vertebrate sensory organs arise from epithelial thickenings called placodes. Along with neural crest cells, cranial placodes are considered ectodermal novelties that drove evolution of the vertebrate head. The anterior-most placode generates the endocrine lobe [adenohypophysis (ADH)] of the pituitary, a master gland controlling growth, metabolism, and reproduction. In addition to known ectodermal contributions, we use lineage tracing and time-lapse imaging in zebrafish to identify an endodermal contribution to the ADH. Single-cell RNA sequencing of the adult pituitary reveals similar competency of endodermal and ectodermal epithelia to generate all endocrine cell types. Further, endoderm can generate a rudimentary ADH-like structure in the near absence of ectodermal contributions. The fish condition supports the vertebrate pituitary arising through interactions of an ancestral endoderm-derived proto-pituitary with newly evolved placodal ectoderm.
Keywords: Endoderm; sekvenování transkriptomu; Cell Lineage; Zebrafish; Animals; buněčný rodokmen; Pituitary Gland, Anterior; RNA-Seq; Single-Cell Analysis; dánio pruhované; analýza jednotlivých buněk; zvířata; endoderm; adenohypofýza